You have to take the question bit by bit.
"Separate 846 into 3 parts."
Therefore: 846 = x + y + z
"The second part is twice the first part."
Therefore: y = 2x
"The third part is triple the second part."
Therefore: z = 3y
But remember that y = 2x so ... 3y = 3(2x) = 6x. Thus z = 6x
Now your subsitute these into the first equation and solve for x:
846 = x + y + z
846 = x + 2x + 6x
846 = 9x
846/9 = x
94 = x
NOW we can substitute this back into the other equations to find the "3 parts"
x = 94
y = 2x = 2(94) = 118
z = 6x = 6(94) = 564
846 = 94 + 118 + 564
2006-10-27 06:42:34
·
answer #1
·
answered by Leah H 2
·
2⤊
1⤋
Let the first part be 'x'
Let the second part be 'y'
Let the third part be 'z'
y = 2x, z= 3y
So, we can say that z = 6x
Now that we have all the derivations we need we can now solve the problem:
x + y + z = 846
Substitute the variables with suitable derivations from above.
Now, our objective is to find 'x'. So we replace y and z with the corresponding values of 'x'.
x + 2x + 6x = 846
9x = 846
x = 846/9
x = 94
The first part is 94.
Now, let's solve for y. We follow the same steps that we did earlier.
x + y + z = 846
94 + y + 3y = 846
4y + 94 = 846
4y = 846 - 94
4y = 752
y = 752/4
y = 188
The second part is 144.
We need no derivations to find 'z'
x + y + z = 846
94 + 188 + z = 846
282 + z = 846
z = 846 - 282
z = 564
The third part is 564.
Let's check the solution:
94 + 188 + 564 = 282 + 564
= 846
Therefore, the solution is correct.
The first part is 94.
The second part is 144.
The third part is 564.
2006-10-27 23:41:44
·
answer #2
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
This is Algebra. I'm not sure about the "four steps" but here is a approach.
846 into 3 parts : 846 = A + B + C
The second part is twice the first : B = 2A
The third part is triple the second : C =3B and therefore C=6A (replacing B with 2A)
So
846= A + 2A + 6A = 9A
So
A=846/9 yielding A=94
plugging in above B = 2A or 188
and C = 3B or 564
For a check 846 = 94 + 188 + 564
2006-10-27 06:44:54
·
answer #3
·
answered by I don't know is OK 2
·
0⤊
1⤋
Think of each part as X… so the parts would be
X 2X 6X
now divided 846 into the total of X, which is nine. So X= 94. Now substitute to get:
94 188 564.
To check the total must be 846. Good luck!
2006-10-27 07:37:50
·
answer #4
·
answered by Pichka 2
·
1⤊
0⤋
Don't know what "using all four steps" means here.
Does "Separate 846 into 3 parts" mean that the sum of the three parts is 846? If so
x = 1st part
2x = 2nd part
3(2x) = 6x = third part
x + 2x + 6x = 846
9x = 846
x = 94
Parts are 94, 188 and 564
2006-10-27 06:37:31
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
The words are the equation:
Separate 846 into 3 parts
846 = a+b+c
the second part is twice the first part
b = 2a
third part is triple the second part
c = 3b
Replace b and c in the first equation with the equivalent value as a function of a and solve for a.
2006-10-27 06:36:13
·
answer #6
·
answered by arbiter007 6
·
1⤊
1⤋
x+2x+(3)2x=846
x+2x+6x=846
9x=846
x=846/9
x=94, 2x=188, 6x=564
2006-10-27 06:47:15
·
answer #7
·
answered by arrizona 3
·
1⤊
0⤋
94
188
564
first part = x
second part = 2x (twice the first part)
third part = 3(2x) or 6X (triple the second part)
x + 2x + 6x = 846
9x = 846
x=94
2x = 188
6x = 564
94 + 188 + 564 = 846 (check)
2006-10-27 06:35:14
·
answer #8
·
answered by Steve 5
·
1⤊
1⤋
l x l 2x l 3*(2x) l
x+2x+3*2x=846=> x=846/9=94
=========================
2006-10-27 06:48:57
·
answer #9
·
answered by Broden 4
·
0⤊
0⤋
the parts be x, 2x, 6x(3*2x)
so that x+2x+6x=846
9x=846
so x=94, 2x=188, 6x=564
are the three parts
2006-10-27 06:36:29
·
answer #10
·
answered by Nature Boy Ash 1
·
1⤊
0⤋